Alterations of Growth Performance and Blood Chemistry in Nile Tilapia (Oreochromis Nuoticus) Affected by Copper Sulfate in Long-Term Exposure - Mutlu, Ekrem; Aydın, Seyit; Kutlu, Banu (Turkish Journal of Fisheries and Aquatic Sciences 15: 487-493 (2015), 2015)
The objective of this study was to evaluate the effects of copper sulfate (CuSO4.(5 H2O)) on the Nile tilapia (Oreochromis niloticus). Median (LC50) and minimum (LC1O) lethal concentrations of copper sulfate on Nile tilapia were determined via acute tests. LC50 values of copper sulfate for the 48th, 72nd and 96th hours were 13.15, 12.95 and 12.85 mg/L, respectively. LC10 values of 12, 11 and 9.5 mg/L were obtained for similar exposure periods (48th, 72nd and 96th hours), respectively. The effects of 1.5 mg/L dose of copper sulfate on growth rate, gross clinical observations and blood biochemical parameters of Nile tilapia were evaluated after 35, 65 and 95 days of exposure periods. The differences of growth rates between control and copper sulfate-exposed groups were not significant (P>0.05) at the end of 35, 65 and 95 days. Continuous exposure of Nile tilapia to 1.5 mg/L concentration of copper sulfate in water solution for three periods (35, 65 and 95 days) decreased the total protein, albumin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), glucose (except the elevation in the exposed group at the end of 95 days period), magnesium (Mg+²), calcium (Ca+²), iron (Fe+²), potassium (K+), sodium (Na+1), chloride (CI-) and phosphate values in serum. The cholesterol, low density lipid (LDL), triglyceride, globulin, creatinine, alkaline phosphatase (ALP), total bilirubin, direct bilirubin, uric acid and blood urea nitrogen (BUN) concentrations in the serum increased in copper sulfate-exposed fish.
Keywords: Nile tilapia, copper sulfate, LC50, LC10, blood, metabolite, electrolyte, growth.